Supervisor support and work engagement of hotel employees in Malaysia - Choo, Ling Suan; Mohd Nasurdin, Aizzat (Emerald Group Publishing Limited, 2016)
Purpose– This study aims to examine the impact of supervisor support and to assess the moderating role of gender on employee work engagement in the context of the Malaysian hospitality industry. Design/methodology/approach– Data were collected from a sample of 438 customer-contact employees in Malaysian upscale hotels and tested using the partial least squares technique.Findings – The findings indicated that supervisor support positively influences work engagement and that this positive relationship was stronger for male employees than female employees.Research limitations/implications– The results highlight that supervisor support plays a critical role in fostering greater employee work engagement. In addition, different approaches need to be utilized by supervisors in supporting their male and female subordinates.Originality/value– This study extends the existing literature by examining the role of gender in moderating the relationship between supervisor support and work engagement, especially within the context of a developing country (i.e. Malaysia), using structural equation modelling.